2018
DOI: 10.1016/j.neuropharm.2018.08.030
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylase KDM6B in the medial prefrontal cortex epigenetically regulates cocaine reward memory

Abstract: Epigenetic remodeling contributes to synaptic plasticity via modification of gene expression, which underlies cocaine-induced long-term memory. A prevailing hypothesis in drug addiction is that drugs of abuse rejuvenate developmental machinery to render reward circuitry highly plastic and thus engender drug memories to be highly stable. Identification and reversal of these pathological pathways are therefore critical for cocaine abuse treatment. Previous studies revealed an interesting finding in which the mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…The lysine demethylase 6B (KDM6B) is upregulated in the mPFC during cocaine withdrawal and is known to regulate drug-associated reward memory. KDM6B inhibition disrupts both, reconsolidation of cocaine-conditioned memory and reinstatement, suggesting dual effects of KDM6B in cocaine drug-seeking behaviour [179]. In alcohol dependence, the upregulation of KDM6B is associated with epigenetic regulation of signalling pathways by a decrease in the H3K27me3 level, consistent with its known demethylase function [180].…”
Section: Addiction and Epigeneticsmentioning
confidence: 68%
“…The lysine demethylase 6B (KDM6B) is upregulated in the mPFC during cocaine withdrawal and is known to regulate drug-associated reward memory. KDM6B inhibition disrupts both, reconsolidation of cocaine-conditioned memory and reinstatement, suggesting dual effects of KDM6B in cocaine drug-seeking behaviour [179]. In alcohol dependence, the upregulation of KDM6B is associated with epigenetic regulation of signalling pathways by a decrease in the H3K27me3 level, consistent with its known demethylase function [180].…”
Section: Addiction and Epigeneticsmentioning
confidence: 68%
“…Another outstanding question is the exact mechanisms by which ACA CaMKII neurons drive the long-term effect of enhanced drug-seeking induced by concurrent Meth and sex, during which we hypothesize key molecular events occur to induce long-term plasticity associated with habitual, dysregulated drug-seeking (Nestler, 2008 , 2014 ; Perrotti et al, 2008 ; Li et al, 2011 ; Muschamp et al, 2012 ; Godino et al, 2015 ; Zhang et al, 2018 ). Previously, we showed that concurrent Meth and sex experience induced long term increases in expression of phosphorylation of MAP kinase (pERK) in ACA CaMKII neurons (Kuiper et al, 2017 ), consistent with long term plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…This plasticity may be a reflection of alterations in afferent signaling to the CaMKII cells, including local inhibitory interneurons (Morshedi and Meredith, 2007 ; Wearne et al, 2017 ). Cellular and epigenetic alterations have been observed in mPFC following chronic Meth (Howell and Kimmel, 2008 ; Shibasaki et al, 2011 ; Li et al, 2014 ) or other psychostimulants (Mychasiuk et al, 2013 ; Zhang et al, 2018 ). Since sexual behavior and drug exposure lead to similar molecular and plasticity mechanisms within NAc and VTA (Beloate and Coolen, 2017 , 2018 ), it is interesting to test if concurrent Meth and sex may cause either additive or synergistic effects on such cellular alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Rats went through procedures in Figure 1 without cannula placement, microinjection or locomotion test. Western blotting was performed as previously described ( Zhang et al, 2018 ). Briefly, brain tissue containing the VLO was rapidly collected after animal anesthesia and decapitation.…”
Section: Methodsmentioning
confidence: 99%